LOCAL CONTENT OF PRIMARY SCHOOL ENGLISH AS A MEANS OF PRESERVING AND DEVELOPING REGIONAL ADVANTAGES AND WISDOM OF THE BANYUWANGI REGION: MUATAN LOKAL BAHASA INGGRIS SEKOLAH DASAR SEBAGAI SARANA PELESTARIAN DAN MENGEMBANGKAN KEUNGGULAN DAERAH DAN KEARIFAN DAERAH BANYUWANGI - Yuli Sugianto; Supono; Ach Zayul Mustain (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research is a study of students’ workbook in 41 elementary School in Banyuwangi City. The study was limited in used topic in each chapter, from the 1st grade to the 6th grade of elementary school. The decree of ministry of education and culture number 79, 2014 used as parameter of this study. The result indicated that from 6 different levels of workbook that is used by the students from 41 elementary schools, none of them took local uniqueness as their topic in workbooks. It also found that from 41 English teachers in 41 schools, researcher chose 20 teachers as data sampling to be observed. Found that most teachers never develop the topic in the workbooks, they used workbooks as what they are. Multicultural in Banyuwangi do not make teachers aware to promote it to their students.